AKTIVITAS PENGHAMBATAN FRAKSI DAUN DELIMA (Punica granatum L.) TERHADAP BAKTERI Mycobacterium tuberculosis - Afrisusnawati Rauf; Nurshalati Tahar; Resnia Resnia (Universitas Islam Negeri Alauddin Makassar, 2019)
Punica granatum L., commonly known as pomegranate, has emerged as a medicinal plant with potential antimicrobial activity. This study aims to identify this activity against the bacteria Mycobacterium tuberculosis. Pomegranate leaf extract is made using solvents (ethanol 96%), then partitioned using n-butanol solvents and fractionated using vacuum liquid chromatography method. After obtaining the fractional results, the inhibitory activity effect of the fraction was studied using the Mycobacterium tuberculosis H37RV strain and compared to commercial antibiotic Isoniazid using the MODS method. Pomegranate leaf fraction shows antibacterial activity against Mycobacterium tuberculosis at a concentration of 1000 ppm, as seen from the absence of cord at such concentrations. Therefore this plant can be an important source of new antimicrobial compounds to treat the bacteria Mycobacterium tuberculosis.